Greek Myth and Fantasy as Portrayed in Black Swan Movie Script by Andrez Heinz - Wanda Firanci; Muarifuddin Muarifuddin; Nurisrafyan Sofian (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2022)
This study aimed to analyze racism in The Man Who Knew Infinity movie using Paradies, Harris, and Anderson's theory. The Man Who Knew Infinity released in 2016 is a film directed by Matthew Brown that features the character of a genius mathematician from India named Srinivasa Ramanujan who wants to publish his formula about mathematics at Trinity College. As an Indian, Ramanujan experienced various acts of racism committed by the British, both mentally and physically. This study used a descriptive qualitative method. The data was collected through four steps, such as watching, screenshotting, note-taking, and identifying the data. The result of this study showed that the main character experienced racism because of his race and nationality. The kinds of racism that the main character experienced namely stereotypes, prejudice, and discrimination.